Growth analysis in chard plants (beta vulgaris l. cicla, cv. pencas blancas) exposed to different light quality (2014)
To determine the effects of light quality on the growth indices of plants, Pencas Blancas cultivar chard plantlets were grown for 2 months under five different light treatments, obtained by filtering sunlight through colored polyethylene films. The treatments included: red, blue, green, yellow and transparent cover colors. A transparent cover (white light) was used as the control. The colored covers affected the plant growth. The plants grown under the yellow cover presented a better behavior with regards to growth, taken as: total dry weight per plant, leaf area, specific leaf area, absolute growth rate, relative growth rate, harvestable dry matter and root to shoot ratio. The dry matter partitioning in the leaves and roots was affected by the light quality, but not in the petioles, with a higher accumulation of dry mass in the leaves of plants grown under the yellow cover. As a consequence of the enhanced leaf area in the plants under the yellow cover, they also had the highest water uptake. On the other hand, the highest net assimilation rate value was found in plants grown under the transparent cover. These results open up the possibility of using yellow colored cover in leafy green vegetables, especially in chard plants grown under controlled conditions.